Gambaran tingkat kecemasan mahasiswa pada masa pandemi covid-19 - Suharti, Sri; Fitri, Feni Elda; Nurlisan, Maya (JOURNAL OF Tropical Medicine Issues, 2025)
Background: At the end of 2019, humanity around the world was shaken by the corona virus pandemic which created panic everywhere. Vinus corona is a virus that attacks the respiratory system. Anxiety (Anxiety) is a manifestation and various mixed emotional processes that occur when experiencing emotional stress (frustration) and inner conflict. Purpose: To describe the level of student anxiety during the COVID-19 pandemic. Method: A descriptive method. Respondents of all students of the Baitul Wisdom akper according to the tena are 95 people on 28-31 May 2021 The instrument used to measure the level of anxiety using the Hi-A questionnaire. Results: 20 student did not experience anxiett (21%), mild anxiety 59 students (62%), moderate anxiety 11 students (12%), severe anxiety 5 students (5%). financial anxiety with a total of with a total 0f 59 students (62%) and the least is the level of severe anxiety with a total 5 students (5%). Conclusion: Students experience anxiety when facing the covid-19 pandemic. Keyword: Anxiety; Covid-19; Students. Pendahuluan: Umat manusia diseluruh dunia Akhir tahun 2019 digoncang dengan pandemi virus corona yang membuat kepanikan dimana-mana. Virus corona adalah virus yang menyerang sistem pernapasan. Kecemasan (Ansietas) adalah manifestasi dari berbagai proses emosi yang bercampur baur dan terjadi ketika mengalami tekanan perasaan (frustasi) dan pertentangan batin. Tujuan: Untuk mengetahui gambaran tingkat kecemasan mahasiswa pada masa pandemi covid-19. Metode: Deskriptif, responden seluruh mahasiswa akper baitul hikmah yang sesuai dengan kriteria berjumlah 95 orang pada tanggal 28-31 Mei 2021. Instrumen yang digunakan untuk mengukur tingkat kecemasan menggunakan kuesioner Hrs-A. Hasil: Mahasiswa yang tidak mengalami kecemasan sebanyak 20 mahasiswa (21%), kecemasan ringan sebanyak 59 mahasiswa (62%), kecemasan sedang sebanyak 11 mahasiswa (12%), kecemasan berat sebanyak 5 mahasiswa (%%). mayoritas mahasiswa memiliki tingkat kecemasan ringan dengan jumlah 59 mahasiswa (62 %) dan yang paling sedikit yaitu tingakat kecemasan berat dengan jumlah 5 mahasiswa (5%). Simpulan: Mahasiswa mengalami kecemasan saat menghadapi pandemi covid-19. Kata Kunci: Covid-19; Kecemasan; Mahasiswa.